Orang Minangkabau dan Batak Mandailing di Nagari Buayan - Febrianto, Adri; Hardi, Etmi; ., Bustamam (Humanus, 2011)
The author described, integration between two ethnics Minangkabau and Batak Mandailing was running at Buayan, a small village in West Sumatera. It caused by the Batak Mandailing adaptation ability and tolerance nature Minangkabau people. The sameness of religion (Islam) is the push factor to their integration. In addition, the long process of socialization that occurs in people Mandailing of Minangkabau cultural trait, as well as the amalgamation and the dominance of Minangkabau culture. It described by consider of some daily activities and special event, like badoncek at marital ceremony. Although the description was not neglect conflict, but conflicts at Buayan were not expanding in society before, and they have the musyawarah as the resolution conflict mechanism. All processes that occur precisely shows the acculturation from Minangkabau cultural trait to the Mandailing. Key words:Â  ethnical working culture, civil servants, civil society, democracy